O professor de geografia e o conhecimento docente: diálogos na construção do conhecimento profissional - Santos, Robson Alves dos (2017)
The formation of the Geography teacher has been studied by several researchers and is considered of fundamental importance for the success of school education. There is a series of knowledge and knowledge that are used by teachers during their professional activity, that is, there are knowledge and knowledge that serve as the basis for the office of being a teacher. The objective of this thesis is to analyze the process of construction of this knowledge and knowledge, as well as the construction of the professionalism of four Geography professors who work in Higher Education in the State of Goiás, two Federal University of Goiás in Goiânia (UFG) and two University State of Goiás (UEG) in Anápolis. It is based on Shulman's studies and his knowledge base for teaching, in which this knowledge is divided into knowledge of specific content, general didactic knowledge, context knowledge and pedagogical knowledge of content. The thesis here is that the teacher-teacher in the context of his teaching practice mediates the dialogue between the teaching knowledge, that is, between the specific knowledge of the discipline with the pedagogical knowledge in the construction of the professional knowledge made effective by the students of the Geography degree in initial formation. It was sought to understand the knowledge that Geography teachers must possess, to develop a work in which there is dialogue and articulation between the various existing teaching knowledge and thus promote their professionalism. The following data collection instruments were used: bibliographical reading, analysis of documents such as the Pedagogical Project of the two courses and analysis of the course plans of the disciplines, observation of the classes offered in the degree courses of the two universities of that field Research and interview with the four teachers observed. The result of the study points out that the formative process of the Geography teacher should be based on a teacher that articulates the teaching knowledge in its training practice, as well as encouraging the future teachers the same attitude, that is, a teacher who possesses and Construct pedagogical knowledge of geographic content in its formation.